(untitled) (Research, Society and Development, 2019)
This paper presents an analysis of noncommunicable chronic diseases (CDNTs) in the literature and aims to analyze the risk of Apolipoprotein E (ApoE) and stroke in the contemporary community. Its objective is to analyze the relationship between Apolipoprotein E and Stroke polymorphism based on the risk analysis between ApoE and Stroke genetic polymorphism. This is a descriptive, exploratory and qualitative study. It is concluded that several authors in their study report the increased risk of stroke with ApoE and its alleles.